Rational Solutions of the Sasano System of Type A₅⁽²⁾ - Matsuda, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
In this paper, we completely classify the rational solutions of the Sasano system of type A₅⁽²⁾, which is given by the coupled Painlevé III system. This system of differential equations has the affine Weyl group symmetry of type A₅⁽²⁾.